Using meta-ethnography to synthesize research on knowledge management and agile software development methodology - Ruiz, Glauco Antonio; Napoleão, Bianca Minetto; de Souza, Érica Ferreira; Felizardo, Katia Romero; Meinerz, Giovani Volnei; da Silva, Patrick Rodrigo; Vijaykumar, Nandamudi L. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Context: Software development processes are considered as knowledge intensive and therefore Knowledge Management (KM) can be applied to efficiently manage the knowledge generated. Agile practices can benefit the software organizations in terms of KM. Some studies have already presented evidence about this relationship. However, the intersection of these two areas still require further more clarification. Objective: This study aims to synthesize research on KM and Agile Software Development (ASD) using the meta-ethnography method. Method: In order to achieve the proposed goal, first, we applied the seven phases of meta-ethnography analysis method on a five articles selected from a tertiary study on KM and ASD. Second, the relations identified between the areas investigated were analysed from interviews with three agile development methodology experts. Results: A relation map that summarizes the synthesis identified between KM, agile values and scrum activities was created. Conclusion: There is a significant contribution in KM and ASD for both software engineering academics and industry.